PUBLIC PROCUREMENT DIGITALISATION AS A MECHANISM FOR TRANSPARENCY AND ANTI-CORRUPTION (CROSS BORDER MANAGEMENT STUDY): A SYSTEMATIC LITERATURE REVIEW - Sebastian; Maria Kalis; M. Irfani Hendri (Al-Shobar Publisher, Yayasan Islam Al-Shobar Rawaurip, 2026)
The digitalisation process in public procurement, which includes systems such as e- procurement, electronic government procurement, digital tendering, online auctions, and the use of analytics with risk modelling, has received considerable attention as an approach for improving transparency, enhancing operational efficiency, and reducing corruption. This systematic literature review aims to synthesize empirical evidence as well as conceptual findings on how the digitalisation of procurement affects four key areas: (1) transparency and accountability; (2) outcomes related to integrity, including anti-corruption measures and fraud prevention; (3) operational efficiency and value for money; and (4) competitive dynamics and supplier participation levels. The PRISMA 2020 protocol was followed for the review. Keywords such as